Hearing results of type III tympanoplasty with or without cartilage augmentation after Canal Wall Down mastoidectomy - Shrestha, BL; Bhattarai, H; Bhusal, CL (Journal of Institute of Medicine Nepal, 2010)
Background: To assess and compare the hearing results in patients undergoing canal wall down mastoidectomy with classical type III tympanoplasty using temporalis fascia alone and with cartilage augmented type III tympanoplasty. Methods: Patients of 5 years of age or more with the diagnosis of Chronic otitis media (squamous) with conductive or mixed hearing loss, needing canal wall down mastoidectomy and with intact and mobile stapes suprastructure at surgery who underwent classical type III tympanoplasty with or without cartilage augmentation were included in the study. Pure tone audiometry (PTA) was performed and evaluated. Post- operative hearing was assessed in terms of average air bone gap (ABG) and size of ABG closure. Post-operative hearing results were compared in between classical type III and cartilage augmented type III tympanoplasty groups. Results: Postoperative PTA-ABG ranged from 15-61.2 dB in classical type III tympanoplasty while the postoperative PTA-ABG ranged from 15-47.5 dB in cartilage augmented type III tympanoplasty. When comparing average post-operative ABG and size of ABG closure between classical and cartilage augmented type III tympanoplasty, cartilage augmented group showed marginally better results but this difference was statistically not significant. Conclusions: Hearing results after type III tympanoplasty varied widely. There was no statistically significant improvement in post-operative hearing results in cartilage augmented when compared to classical type III tympanoplasty, suggesting possibility of the effects of multiple other factors. Key words: Air bone gap, air bone gap closure, canal wall down (CWD) mastoidectomy, cartilage augmented type III tympanoplasty, classical type III tympanoplasty, chronic otitis media (squamous). The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, August, 2009; 31:2 22-27